Hubungan antara Kelimpahan Ikan Saluang (Rasbora argyrotaenia Blkr) dengan Populasi Fitoplankton di Dataran Banjir Sungai Rungan Kalimantan Tengah - Bambang Sulistiyarto (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
This study aims to determine the relationship between saluang fish abundance and phytoplankton abundance. The study was conducted at the rainy and dry season in the Rungan river floodplain, Central Kalimantan. 904 fishes (total weight 6642.5 grams) were caught during the study. 54 species of phytoplankton obtained during sampling, which dominated by Chlorophyceae and Bacillariophyceae groups. Regression analysis showed a significant relationship between Saluang fish abundance and Bacillariophyceae abundance (R2 = 82,7% , p = 0,0001). Phytoplankton of Bacillariophyceae can be used as a good predictor for saluang fish abundance in the Rungan river floodplain.